Case Report: Prenatal Diagnosis of a Fetus With Harlequin Ichthyosis Identifies Novel Compound Heterozygous Variants: A Case Report - Liu, Jiao; Zhang, Xingyu; Wang, Weilan; Lan, Xiaofang; Dong, Minyue; Yan, Kai; Lei, Yongliang; Chen, Penglong; Yang, Mufeng; Shan, Qunda; Jin, Chunlei (Frontiers in Genetics, 2021)
Background Harlequin ichthyosis (HI) is the most severe form of the keratinizing disorders, and it is characterized by whole-body hard stratum corneum. ABCA12 has been identified as the major disease-causing gene of HI. Methods A case of HI was prenatally diagnosed by ultrasonography and genetic tests. The fetus had been found with dentofacial deformity and profound thickening of the palm and plantar soft tissues. Chromosomal microarray analysis (CMA) and whole exome sequencing (WES) were then performed on the amniotic fluid to identify germline pathogenic variants for the fetus. Candidate variants were verified by Sanger sequencing. Results Compound heterozygous frameshift variants (p.Q719QfsX21; p.F2286LfsX6) of ABCA12 were identified for the fetus, suggesting the former variants were maternally inherited and the latter paternally inherited. The fetus was terminated. Conclusion A prenatal molecular diagnosis is an important approach for the prevention of HI. In the study, we provided a successful case of genetic counseling for a family with an HI baby.